The Great War and the Anthropocene: Empire and Environment, Soldiers and Civilians on the Eastern Front - Jobst, Kerstin S; Nagornaia, Oksana; von Lingen, Kerstin (History of Warfare, 2024)
This volume places the Eastern, especially the Austro-Russian, fronts of the Great War centre stage, examining the little-known environmental and spatial dimensions in the history of the war. The focus is particularly on the Austrian crown land of Galicia, which was transformed from a neglected periphery into a battleground of three imperial armies, and where for the first time, nature was a key protagonist. The book balances contributions by emerging and established scholars, and benefits from a multi-language approach, expertise in the field, and extensive archival research in national archives. Contributors are Hanna Bazhenova, Gustavo Corni, Iaroslav Golubinov, Kerstin Susanne Jobst, Tomasz Kargol, Alexandra Likhacheva, Oksana Nagornaia, David Novotny, Christoph Nübel, Gwendal Piégais, Andrea Rendl, Kamil Ruszała, Nicolas Saunders, Kerstin von Lingen, Yulia Zherdeva, and Liubov Zhvanko.